Liquid Metal‐Based Transient Circuits for Flexible and Recyclable Electronics. (29th January 2019) - Teng, Long; Ye, Shichao; Handschuh‐Wang, Stephan; Zhou, Xiaohu; Gan, Tiansheng; Zhou, Xuechang
Abstract: Transient electronics, arising electronic devices with dissolvable or degradable features on demand, is still at an early stage of development due to the limited choices of materials and strategies. Herein, a facile fabrication method for transient circuits by the combination of room‐temperature liquid metals (RTLMs) as the electronic circuit and water‐soluble poly(vinyl alcohol) (PVA) as the packaging material is reported. The as‐made transient circuits exhibit remarkable durability and stable electric performance upon bending and twisting, while possessing short transience times, owing to the excellent solubility of PVA substrates and the intrinsic flexibility of RTLM patterns. Moreover, the RTLM‐based transient circuit shows an extremely high recycling efficiency, up to 96% of the employed RTLM can be recovered. As such, the economic and environmental viability of transient electronics increases substantially. To validate this concept, the surface patterning of RTLMs with complicated shapes is demonstrated, and a transient antenna is subsequently applied for passive near‐field communication tag and a transient capacitive touch sensor. The application of the RTLM‐based transient circuit for sequentially turning off an array of light‐emitting‐diode lamps is also demonstrated. The present RTLM‐based PVA‐encapsulated circuits substantially expand the scope of transient electronics toward flexible and recyclable transient systems. Abstract : Flexible and recyclable transient circuits are fabricated by employing room‐temperature liquid metals as the electronic circuit and water‐soluble poly(vinyl alcohol) as the packaging material. The as‐made transient circuits are successfully applied to various electronic devices, including near‐field communication, capacitive touch sensors, and transient circuits to allow sequentially turning off an array of light‐emitting‐diode lamps.